Caliko: An Inverse Kinematics Software Library Implementation of the FABRIK Algorithm. Issue 1 (9th September 2016) - Lansley, Alastair; Vamplew, Peter; Smith, Philip; Foale, Cameron
The Caliko library is an implementation of the FABRIK (Forward And Backward Reaching Inverse Kinematics) algorithm written in Java. The inverse kinematics (IK) algorithm is implemented in both 2D and 3D, and incorporates a variety of joint constraints as well as the ability to connect multiple IK chains together in a hierarchy. The library allows for the simple creation and solving of multiple IK chains as well as visualisation of these solutions. It is licensed under the MIT software license and the source code is freely available for use and modification at:https://github.com/feduni/caliko